Pengaruh Kompensasi, Kepemimpinan, dan Lingkungan Kerja Fisik terhadap Kepuasan Kerja Karyawan PT. Cargo Asas International, Denpasar - Indrawan, Dewa Cahyadi; Dewi, AA Sagung Kartika (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
Satisfaction of job is an positive feeling about work of samone representing result of from a its characteristic evaluation. Statisfaction of job is pleasant situation emotionally which is yielded from asseeement of work of someone, effective reaction to work of someone, and attitude to work of someone. Satisfaction of  sameone job base on expectation of individual and accomplishmen of requirement which in fact from dimiciling it. Satisfaction of jobhappened when requirement and exemtion relate to work remain to fullfilled. The purpose of this study is to determine whether the compensation, leadership, and physical work environment affects employee satisfaction simultaneously and also partial. Amount of  responder in this research counted 37 employees people. Quantitative analysis method the used is test of R simultan, significance test coefficient of regresi by parsial and regresi analisis. Result of research indicate that compensation, leadership, and environment work pysical by simultan have relation of satisfaction of job. By parsial compensation variable, leadership, and environment work also have an effect on positive to satisfaction of employess job.
Keywords: Keyword : Satisfaction of job, compensation, leadership, environment of physical job